2022
DOI: 10.35196/rfm.2000.1.49
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMACIÓN DE VARIANZA ADITIVA Y HEREDABILIDAD EN DOS POBLACIONES DE TOMATE DE CÁSCARA (Physalis ixocarpa Brot.)

Abstract: El objetivo del presente trabajo fue estudiar el cambio en la varianza aditiva y la heredabilidad de los caracteres peso y número de frutos después de seis ciclos en selección de la variedad “Rendidora” de tomate de cáscara (Physalis ixocarpa Brot.). Para realizar lasestimaciones se empleó la metodología de medios hermanos maternos recientemente propuesta. Después de seis ciclos de selección, la media de rendimiento mostró un cambio estadístico significativo promedio de 300 g/planta con una ganancia por ciclo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Relatively high CV G and h 2 estimates associated with higher gains for the traits of interest indicate the importance of additive gene action (Narayan et al, 1996), enhancing the selection procedure. Grajales et al (2000) reported lower heritability values through an improved material of P. ixocarpa compared to our finding, ranging from 0.26 to 0.23 for fruit yield and number of fruits per plant, respectively. Additionally, Ara et al (2009) and Saeed et al (2007) showed high heritability followed by high genetic gain for the total number of fruits per plant.…”
Section: Mean Performance Of Selected Individualscontrasting
confidence: 97%
See 1 more Smart Citation
“…Relatively high CV G and h 2 estimates associated with higher gains for the traits of interest indicate the importance of additive gene action (Narayan et al, 1996), enhancing the selection procedure. Grajales et al (2000) reported lower heritability values through an improved material of P. ixocarpa compared to our finding, ranging from 0.26 to 0.23 for fruit yield and number of fruits per plant, respectively. Additionally, Ara et al (2009) and Saeed et al (2007) showed high heritability followed by high genetic gain for the total number of fruits per plant.…”
Section: Mean Performance Of Selected Individualscontrasting
confidence: 97%
“…While the marketable yield per feddan gave the highest gain by the selection, (32.33%) based on fewer values of both CV G and h 2 . In contrast, high values of CV G (coefficient of genetic variation) and h 2 have been reported in similar original population is necessary to allow the formation of a proportion of individuals whose mean is higher than the original population mean so that when multiplied by heritability, the result will be optimal (Grajales et al, 2000). Among the objectives of the current investigation was to identify genotypes with higher fruit yield and fruit flavor quality.…”
Section: Mean Performance Of Selected Individualsmentioning
confidence: 93%